Cocirculation of Leptospira spp. and multiple orthohantaviruses in rodents, Lithuania, Northern Europe. Issue 5 (28th February 2022) - Jeske, Kathrin; Schulz, Jana; Tekemen, Duygu; Balčiauskas, Linas; Balčiauskienė, Laima; Hiltbrunner, Melanie; Drewes, Stephan; Mayer‐Scholl, Anne; Heckel, Gerald; Ulrich, Rainer G.
Abstract: In Europe, zoonotic Leptospira spp. and orthohantaviruses are mainly associated with specific rodent hosts. These pathogens cause febrile human diseases with similar symptoms and disease progression. In Lithuania, the presence of Dobrava‐Belgrade orthohantavirus (DOBV), Tula orthohantavirus (TULV) and Leptospira spp. in rodent reservoirs is still unknown, and Puumala orthohantavirus (PUUV) was detected in bank voles ( Clethrionomys glareolus ) at only one site. Therefore, we collected and screened 1617 rodents and insectivores from Lithuania for zoonotic (re‐)emerging Leptospira and orthohantaviruses. We detected Leptospira DNA in six rodent species, namely striped field mouse ( Apodemus agrarius ), yellow‐necked mouse ( Apodemus flavicollis ), bank vole, common vole ( Microtus arvalis ), field vole ( Microtus agrestis ) and root vole ( Microtus oeconomus ). Leptospira DNA was detected with an overall mean prevalence of 4.4% (range 3.7%–7.9% per rodent species). We detected DOBV RNA in 5.6% of the striped field mice, PUUV RNA in 1% of bank voles and TULV RNA in 4.6% of common voles, but no Leptospira DNA in shrews and no hantavirus‐ Leptospira coinfections in rodents. Based on the complete coding sequences of the three genome segments, two distant DOBV phylogenetic lineages in striped field mice, one PUUV strain in bank voles and two TULV strains in common voles were identified. The Leptospira prevalence for striped field mice and yellow‐necked mice indicated a significant negative effect of the distance to water points. The detection of (re‐)emerging human pathogenic Leptospira and three orthohantaviruses in rodent reservoirs in Lithuania calls for increased awareness of public health institutions and allows the improvement of molecular diagnostics for pathogen identification.